Hydrocarbon accumulation conditions and favorable exploration zones in the Lunpola Basin, Tibet - Zhang, Yunbo; Wang, Rui; Xu, Jie; Wu, Xinhe; Li, Yinglie; Lin, Yanhua; Wang, Buqing (Frontiers in Earth Science, 2023)
By systematically reviewing and summarizing the previous studies on the petroleum geology of the Lunpola Basin, combined with the latest oil and gas exploration results, the oil and gas accumulation conditions of this basin are summarized, and the favorable zones with the most exploration potential are pointed out. The results show that: ① The Paleogene mainly develops three sets of source rocks, including Niu-1 section, Niu-2 section and lower Niu-3 subsection. Among them, the source rock of Niu-2 section is the best. However, the source rock of Niu-1 section is only developed in the Jiangjiacuo depression. The thickness and abundance of the source rocks have decreased eastward. The organic matter are mainly Type I and Type II1, with a maturity of 0.58~1.08%. ② The study area is dominated by clastic rock reservoirs, which can be divided into three types according to the strata distribution, and the overall reservoir conditions are not good. The ultra-low porosity and ultra-low permeable fracture-porous reservoirs are developed. ③ Three sets of seals are mainly developed in the Lunpola Basin, including two regional seals of the middle Niu-2 subsection and Dingqinghu section, and a direct seal of upper Niu-2 subsection. These three sets of seals are well developed and have good preservation conditions in the relatively stable central depression and the footwall of thrust nappe structural belt . ④ The oil and gas reservoirs in the Lunpola Basin have the distribution law of “structural traps in the north and south, and lithologic traps in the center”. Structural traps are mainly distributed in the thrust nappe belt in the north and the Changshan uplift in the south, forming “self-generation and self-storage” or “lower-generation and upper-storage” reservoirs. While lithologic traps are mainly distributed in the central sag, forming “self-generation and self-storage” reservoirs. ⑤ The source-reservoir-caprock combination conditions are good in the structural traps in the footwall of the northern thrust nappe belt and the lithologic traps in the southern slope belt of Jianjiacuo depression, , and they are the most favorable oil and gas exploration zones in the Lunpola Basin.